Moral Development Program for Foster Children at Al Washliyah Binjai Women's Orphanage - Budianti, Yusnaili; Salminawati, Salminawati; Isminar, Isminar (Budapest International Research and Critics University, 2022)
The aims of this study are to find out moral development program for foster children at al washliyah binjai women's orphanage. The type of research is a qualitative analysis research. The result of this study shows that moral development for foster children at the Al Washliyah Binjai women's orphanage can be seen in the morals of foster children who have lived in the orphanage for a long time. Those who are more senior in general have been able to have good morals such as being able to istiqamah in obedience to worship, polite, patient and sincere, disciplined, simple, independent, have a sense of ukhuwah Islamiyah, and mujahadah in living life. Moral development for foster children at the Al Washliyah Binjai women's orphanage can be said to have been running as it should. The coaching can be measured by changes and differences in better morals in foster children who have lived for a long time compared to foster children who have just joined. If you look at coaching through activity programs such as congregational prayers, it can be said that it is quite good because even though the administrators or orphanages are not in the dormitory, they still pray together even though some of them pray individually. Schools in madrasas also carry out fostering the morals of foster children because they study in an Islamic environment so that they can be carried away by that environment.